2013
DOI: 10.1017/s0028688513000131
|View full text |Cite
|
Sign up to set email alerts
|

Dating the Death of Jesus: Memory and the Religious Imagination

Abstract: After discussing the scholarly preference for dating Jesus' crucifixion to  April  CE, this article argues that the precise date can no longer be recovered. All we can claim with any degree of historical certainty is that Jesus died some time around Passover (perhaps a week or so before the feast) between  and  CE. The emergence of the Johannine tradition (in which Jesus died on the day of Preparation) and the Markan tradition (in which Jesus died on the Passover itself) are explored through the lens of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…There are no other possibilities, as it can be deduced from the most important astronomical studies on Jesus' crucifixion (Fotheringham 1934;Schafer 1990;Finegan 1998;Humphreys and Waddington 1992;Bond 2013). The results of the analysis are summarized in Table 1.…”
Section: An Unheard-of Literary Workmentioning
confidence: 97%
“…There are no other possibilities, as it can be deduced from the most important astronomical studies on Jesus' crucifixion (Fotheringham 1934;Schafer 1990;Finegan 1998;Humphreys and Waddington 1992;Bond 2013). The results of the analysis are summarized in Table 1.…”
Section: An Unheard-of Literary Workmentioning
confidence: 97%
“…29 It means that scholarly conclusions about the historical Jesus and (in)accuracy of the gospels must arise out of this larger process of constructing how early Christianity came to be in light of our current knowledge about it. First efforts to carry out historical Jesus research along these lines can be found in the work of Le Donne (2009: 248-57; 2011a: 120-32; 2011b: 186-204), Keith (2011a: 165-92; 2014: 111-57), Bond (2013: 461-75) and Thate (2013: 247-89). 30…”
Section: Two Models For Historical Jesus Research In Contemporary Discussionmentioning
confidence: 99%
“…Consequently, the Nativity, set at least four years before the beginning of the Christian Era, has influenced most scholars who have preferred setting the crucifixion on 7 April 30, among the dates astronomically allowed (La Greca & De Caro, 2017;Finegan, 1998;Fotheringham, 1934;Nothaf, 2012a;Schaefer, 1990;Bond, 2013;Humphreys & Waddington, 1983;Humphreys & Waddington, 1992;Ruggles, 1990). This dating aims at recovering compatibility with historical and chronological constraints deduced by the Gospels, such as Jesus' age of about thirty years when his public ministry began (Luke,3,23) and three years of public ministry deducible by John's Gospel, leading to an age of about 33 years at death.…”
Section: The Debate On Dating Jesus' Birth and Deathmentioning
confidence: 99%
“…In Table 1 we have listed the possible dates of Jesus' death, according to astronomical calculations, most of which have been discussed in (La Greca & De Caro, 2017;Finegan, 1998;Fotheringham, 1934;Nothaf, 2012a;Schaefer, 1990;Bond, 2013;Humphreys & Waddington, 1983;Humphreys & Waddington, 1992;Ruggles, 1990). The dates when Nisan 14 was Friday (according to John) or Nisan 15 (according to the Synoptics) are highlighted in bold.…”
Section: Possible Crucifixion Datesmentioning
confidence: 99%
See 1 more Smart Citation